MAGNETIC RESONANCE ANGIOGRAPHY IN CHILDREN WITH ARTERIAL HYPERTENSION - A SINGLE-CENTER EXPERIENCE - Cvetković, Mirjana (Medical Research, 2023)
Introduction: Renal blood vessel (RBV) stenosis is the cause of secondary arterial hypertension (AH)  in 10% of children. Digital subtraction angiography (DSA) is the gold standard for the diagnosis of RBV stenosis. Many authors suggest MR angiography (MRA), a non-invasive method without radiation, as an adequate diagnostic method. Our aim was to analyze the experience of our center in using MRA in children with AH.Method: This retrospective study included 148 patients hospitalized at University Children's Hospital in Belgrade, due to AH. After initial examination, patients underwent DSA and/or MRA.Results: According to current guidelines, DSA was performed in patients with highly suspected RBV stenosis and the diagnosis was confirmed in 13/29 (45%). Diagnostic MRA was done in 116/119 (97.5%) patients, and control MRA after therapeutic revascularization in 3/119 (2.5%). In 4/116 (3.5%) patients, the findings indicated RBV stenosis, and in 44/116 (38%) some other abnormality of the kidney parenchyma and urinary tract or RBV varieties. After MRA, DSA was performed in 7/116 (6%) patients (4 with RBV stenosis on MRA and 3 with clinical suspicion of RBV stenosis), but all findings were normal.Conclusion: According to the results, it is justified to perform a diagnostic MRA before DSA in children with highly suspected RBV stenosis, in order to avoid DSA, as an invasive procedure with radiation, in some patients with normal findings. Also, over time, we would have a clearer view in the sensitivity and specificity of MRA as a diagnostic method in RBV stenosis in children.
Keywords: Renal blood vessel stenosis, Arterial hypertension, MR angiography, Digital subtraction angiography, Children